Diagnosis and cellophane banding surgery for extrahepatic congenital portosystemic shunt in a domestic short hair cat - Annisa Madyanti Gemimastiti; Ivan Satriawan (ARSHI Veterinary Letters, 2024)
Congenital portosystemic shunts (CPSS) in cats are significant vascular anomalies in which abnormal connections between the portal venous system and systemic circulation allow portal blood to bypass the liver, leading to clinical manifestations such as hepatic encephalopathy and growth retardation due to inadequate toxin filtration. This case study describes a four-month-old male domestic short-hair cat that presented with loss of appetite, weight loss, aggression, excessive drooling, and frequent vomiting. Diagnostic evaluations included physical examination, radiography showing a microhepatic condition with cranial displacement of the stomach, and ultrasonography with colour Doppler, revealing a shunt between the portal vein and the caudal vena cava. Following surgical correction using the cellophane banding method, the cat showed significant clinical improvement and normalisation of ammonia levels, emphasising the importance of precise diagnostic techniques and adequate surgical management in the treatment of CPSS in felines.